Implementation the School Literacy Movement (GLS) within an Independent Curriculum for Lower Primary School Grades - Hidayati, Siti Nur; Wardana, Ludfi Arya; Jannah, Faridahtul (LJPI UI Bunga Bangsa Cirebon, 2024)
Purpose: This research aims to explain the status of the implementation of the School Literacy Movement (GLS) within the framework of the independent curriculum in the lower classes of SDN Curahgrinting 3 Probolinggo. Methods: This research uses qualitative research methods. This study focuses on the perceptions of school principals, teachers, and students regarding the implementation of GLS, as well as teachers' strategies for overcoming related challenges. The five subjects examined included the school principal, class I and II teachers, and class I and II students. Data collection was carried out through observation, interviews and documentation, then analyzed through data reduction, presentation and verification. Results: The findings show that the implementation of GLS at SDN Curahgrinting 3 Probolinggo, especially in classes I and II, is in the habituation and development stage. Evaluation strategies primarily include formative evaluation and open communication with students and parents. Conclusion: The habituation stage is carried out with activities that last 30 minutes to one hour, establishing a reading corner, and providing additional classes. Furthermore, during the development stage, communal reading activities in the classroom and library. This research highlights the evolving nature of GLS integration in the independent curriculum. These insights contribute to understanding the direction and implications of implementing GLS in primary education, as well as guiding future initiatives in the promotion of literacy within an educational framework.